The Ratio of Platelets to Lymphocytes Predicts the Prognosis of Metastatic Colorectal Cancer: A Review and Meta-Analysis - Jinming Wang; Jing Li; Sheng Wei; Jie Xu; Xiaohui Jiang; Lei Yang (Gastroenterology Research and Practice)
Background. In recent years, the incidence of colorectal cancer (CRC) has continued to increase. Although the overall prognosis of CRC has improved with the continuous improvement of the level of treatment, the prognosis of metastatic colorectal cancer (mCRC) is still poor. The purpose of our study is to explore the prognostic value of platelet to lymphocyte ratio (PLR) in mCRC. Methods. The PubMed, Web of Science, and Embase (via OVID) were systematically searched to obtain all relevant research. We used hazard ratio (HR) with 95% confidence interval (CI) to assess the associations of PLR and overall survival (OS) and progression free survival (PFS). Results. A total of twelve studies containing 1452 patients were included in this meta-analysis. Pooled analysis showed that high levels of PLR were associated with poor OS (HR: 1.72, 95% CI: 1.27–2.33, and P<0.01) and PFS (HR: 1.64, 95% CI: 1.16–2.31, and P=0.033). Conclusion. Our analysis suggested that high levels of PLR pretreatment may be an effective predictive biomarker for the prognosis of mCRC patients.